Analisis Finansial Usaha Budidaya Rumput Laut dan Nilai Tambah Tepung Karaginan di Kecamatan Kei Kecil, Kabupaten Maluku Tenggara - Anna Kartika Ngamel (IPB University, 2012)
The purpose of this study was to calculate the financial analysis of seaweed cultivation operation and count the number of value-added processing karaginan flour mill in the District of Southeast Maluku Regency Kei Kecil. The method used in this study is descriptive with qualitative and quantitative approaches. Determination of the location of the study was conducted purposively with its population was seaweed farmers from ten villages in Kei Kecil as the villages of seaweed production centers. The method of analysis used is the operation analysis of financial and added value analysis method Hayami. The results showed that the cultivation of seaweed and flour mills karaginan feasible to develop. The ratio of added value of 9.05% and in 1997 Hubeis magnitude of the ratio of value added is calculated in accordance with the criteria of low added value ratio <15%.Keywords: Financial Analysis, Added-value, Seaweed, Flour Caragenan